Development of a territory-wide household-based composite index for measuring relative distribution of households by economic status in individual small areas throughout Hong Kong - Eva L.H. Tsui; Philip L.H. Yu; K. F. Lam; Kelvin K.Y. Poon; Adam C.M. Ng; K. Y. Cheung; Winnie Li; Michael L.H. Leung; David H.Y. Lam; James L.Y. Cheng; Sharon P.W. Ng (BMC Public Health)
Abstract Background Many countries have developed their country/nation-wide multidimensional area-based index on deprivation or socioeconomic status for resource allocation, service planning and research. However, whether each geographical unit proxied by a single index is sufficiently small to contain a relatively homogeneous population remains questionable. Globally, this is the first study that presents the distribution of domestic households by the territory-wide economic status index decile groups within each of the 2,252 small subunit groups (SSUGs) throughout Hong Kong, with a median study population of 1,300 and a median area of 42,400 m2. Methods The index development involved 248,000 anonymized sampled household-based data collected from the population census, representing 2·66 million domestic households and 6·93 million population in mid-2021. Our composite index comprises seven variables under income-/wealth-related and housing-related domains with weights determined using the analytic hierarchy process. After ranking all households from the most to the least well-off according to the numeric/ordinal value of each variable and then calculating their weighted rank scores, they were segregated into ten deciles from D1 (top 10% most well-off) to D10 (bottom 10%). Their relative distribution was summarized in a three-dimensional ternary plot to distinguish patterns across the 2,252 SSUGs within the 18 administrative districts. Results In Hong Kong, of the 2,252 SSUGs, only one-quarter contain a homogeneous composition of households with similar economic status, while the other three-quarters are heterogeneous to varying extents. Of the 18 administrative districts, only two are concentrated with more homogeneously well-off SSUGs. Conclusions Small-sized geographical units may contain a heterogeneous composition of households with diverse economic statuses, underlying the need for more precise information to quantify their relative distribution. Results of this study are disseminated via an online interactive map dashboard ( https://experience.arcgis.com/experience/b4c7643feb9043eb94b3add386c4b71c/ ) which can serve as a versatile planning tool capable of performing analysis at different varying geographic scales for community-based resource prioritization, service planning and research across different domains.